World view in the novel (Ewarai Prwana) by Bakhtiyar Ali from Lucian Goldman's perspective - Tanya Asad Mohammad Salih (Zanco Journal of Humanity Sciences)
This research is titled (World view in the novel (Ewarai Prwana) by Bakhtiyar Ali from Lucian Goldman's perspective). The research is an attempt to shed light on an important and somewhat new topic in the world of Kurdish literary criticism, as it did not gain its special attention in Kurdish literary criticism. Originally literary works are an expression of the literary worldview.